How to Use Kinship Greetings in Everyday Life in Minangkabau and It`S Implementation in Scriptwriting - Maryelliwati Maryelliwati; Efrinon Efrinon; Wahida Wahyuni; Ninon Syofia (Aksara, 2022)
This research problem is to reveal and describe how the people in Nagari Mungka use the patterns of kinship greeting forms in the Minangkabau language as a case example. Mungka is one of the areas that, until now, still uses the values of the Minangkabau language and culture well, so it is necessary to see how they use the greeting language in their daily kinship. Data were collected using questionnaires, interviews, cross-checks, data collection, and recording. In addition, free and unbound listening techniques were also used to collect data using the form of kinship greetings in a conversation. The analysis method was using sorting and classifying the data based on the type or category of kinship greeting forms through the kinship system in Minangkabau. The analysis results show the characteristics of Minangkabau culture in using patterns of kinship greeting forms such as pronouns, titles, kinship greetings, and kinship greetings added with pronouns and adjectives. Based on the findings, if a scriptwriter wants to write a traditional script in kinship greetings, it can refer to the use of kinship in Minangkabau. AbstrakMasalah penelitian ini adalah mengungkap dan mendeskripsikan bagaimana masyarakat di Nagari Mungka menggunakan pola-pola sapaan kekerabatan dalam bahasa Minangkabau sebagai contoh kasus. Mungka merupakan salah satu daerah yang sampai saat ini masih menggunakan nilai-nilai bahasa dan budaya Minangkabau dengan baik, sehingga perlu dilihat bagaimana mereka menggunakan bahasa sapaan tersebut dalam pergaulan sehari-hari. Data dikumpulkan dengan menggunakan angket, wawancara, cek silang, pengumpulan data, dan pencatatan. Selain itu, teknik menyimak bebas dan tidak terikat juga digunakan untuk mengumpulkan data berupa sapaan kekeluargaan dalam percakapan. Metode analisis menggunakan pemilahan dan pengklasifikasian data berdasarkan jenis atau kategori bentuk sapaan kekerabatan melalui sistem kekerabatan di Minangkabau. Hasil analisis menunjukkan ciri-ciri budaya Minangkabau dalam menggunakan pola bentuk sapaan kekerabatan seperti kata ganti, gelar, sapaan kekerabatan, dan sapaan kekerabatan ditambah dengan kata ganti dan kata sifat. Berdasarkan temuan tersebut, jika seorang penulis naskah ingin menulis naskah adat dalam sapaan kekerabatan, dapat merujuk pada penggunaan kekerabatan di Minangkabau.